Analisis Kontribusi BUMDes Inahuk terhadap Pendapatan Asli Desa Mata Air Tahun 2024, Kecamatan Kupang Tengah - Mariana Jesika Mau; Fransiska Wea; Clarita Nanci Fatin; Tasya Manek (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the contribution of Inahuk Village-Owned Enterprise (BUMDes) to the Original Village Income (PADes) of Mata Air Village in 2024. The research was conducted to address the main problem that the village’s economic potential, particularly the Sulamanda Beach asset, has not been optimally managed due to the non-functioning of BUMDes in recent years. A qualitative descriptive approach was applied, supported by interviews with the Village Head, BUMDes administrators, and community members, as well as observations and document analysis. Data were analyzed using the Miles and Huberman model through data reduction, presentation, and conclusion drawing. The findings show that BUMDes Inahuk did not provide any financial contribution to PADes in 2024. This condition stems from inactive business units, the absence of financial reports since 2023, weak managerial performance, and a lack of accountability from the management. The village government also failed to implement adequate supervision, resulting in operational stagnation. As a consequence, the management of Sulamanda Beach was temporarily taken over by the village government to ensure that village revenue could still be collected. These results highlight the gap between the expected role of BUMDes and its actual operation. Strengthening governance, improving managerial capacity, and clarifying institutional roles are essential steps to revitalize BUMDes Inahuk so it can contribute meaningfully to PADes and support local economic development.